RESPON PASAR MODAL PADA PERISTIWA PERTEMUAN IMF DAN BANK DUNIA DI INDONESIA - Danu Rizky Saputra (BISMA: Jurnal Bisnis dan Manajemen, 2021)
This study aims to determine the presence or absence of abnormal returns, cumulative abnormal returns, and trading volume activity at the IMF and World Bank meetings in Indonesia with an event study on food and beverage manufacturing companies terdaftar on the Indonesia Stock Exchange (IDX). The population used was 14 manufacturing companies in the food and beverage sub-sector. The analytical technique used was a comparative study comparing seven days before and seven days after the event. The results showed no abnormal return at the mean value of significance. There was a significant difference in cumulative abnormal returns in the days before and after the IMF and World Bank meeting in Indonesia in food and beverage sub-sector manufacturing companies terdaftar on the IDX. In addition, stock trading volume activity on the day before the IMF and World Bank meeting in Indonesia increased but decreased after the event. The results of testing the difference in stock trading volume activity showed no significant difference for each pair of days.